B cell memory: building two walls of protection against pathogens - Akkaya, Munir; Kwak, Kihyuck; Pierce, Susan K. (Nature reviews. Immunology, 2020)
Surviving a single infection often results in lifelong immunity to the infecting pathogen. Such protection is mediated, in large part, by two main B cell memory ‘walls’ — namely, long-lived plasma cells and memory B cells. The cellular and molecular processes that drive the production of long-lived plasma cells and memory B cells are subjects of intensive research and have important implications for global health. Indeed, although nearly all vaccines in use today depend on their ability to induce B cell memory, we have not yet succeeded in developing vaccines for some of the world’s most deadly diseases, including AIDS and malaria. Here, we describe the two-phase process by which antigen drives the generation of long-lived plasma cells and memory B cells and highlight the challenges for successful vaccine development in each phase. The authors discuss the formation of two main ‘walls’ of B cell memory to protect against pathogen reinfection. The first wall comprises high-affinity antibodies produced by long-lived plasma cells, while the second wall is formed by memory B cells.